2019
DOI: 10.1002/jrs.5642
|View full text |Cite
|
Sign up to set email alerts
|

Raman evolution of order–disorder phase transition in multiaxial molecular ferroelectric thin film

Abstract: Multiaxial molecular ferroelectrics (MFe) attain great attention due to their number of equivalent ferroelectric axes, an essential characteristic for many applications of these polar polycrystalline materials. Here we report a systematic approach to reveal the temperature‐dependent Raman spectroscopic investigation of the vibrational properties of a [Hdabco]ReO4 (dabco = 1,4‐diazabicyclo[2.2.2]octane), a multiaxial MFe thin film. The Raman spectra allowed to obtain information relative to the change in molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We performed a variable temperature Raman spectroscopy test in order to investigate the overall properties of compound 1 in relation to its temperature dependence. 37,38 Fig. S6 † shows the Raman spectra of compound 1 in the 3500-200 cm −1 region.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a variable temperature Raman spectroscopy test in order to investigate the overall properties of compound 1 in relation to its temperature dependence. 37,38 Fig. S6 † shows the Raman spectra of compound 1 in the 3500-200 cm −1 region.…”
Section: Resultsmentioning
confidence: 99%
“…Widelicka et al [ 169 ] carried out spectroscopic investigations of the new anhydrous proton‐conducting compound of pyrazole with oxalate acid where it was shown that dominant types of salt interactions are medium strength hydrogen‐bonding interactions. Zafar et al [ 170 ] used Raman to study the order–disorder phase transition in multiaxial molecular ferroelectric thin films.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…These materials can show rapid switching with frequencies of up to 263 kHz. Moreover, molecular rotations in response to an applied electric field or mechanical force can result in large shear piezoelectric responses . These types of molecular crystals can also crystallize in pseudo high-symmetry structures, thus allowing multiaxial polarization, with as many as 24 equivalent axes. Multiaxial polarization allows the spontaneous polarization to be aligned in a desired direction in polycrystalline materials and could allow for multibit storage in single crystals …”
Section: Introductionmentioning
confidence: 99%